GÊNEROS RADIOJORNALÍSTICOS: Análise da Rádio Eldorado de São Paulo - Lucht, Janine Marques Passini (2009)
This thesis is part of the mass communication field of knowledge. The focus is within media studies and the goal is to create a new classification strategy for journalistic genres on Brazilian radio. The method for this study begins with an analysis of current literature on the subject from which classification categories were defined. These categories were then applied to the actual content of three programs on Radio Eldorado AM Sao Paulo, one of the most traditional journalistic broadcasters in Brazil.(AU)